ANALISIS SISTEM DAN PROSEDUR PENGADAAN BARANG DAN JASA DI KOMISI PEMILIHAN UMUM PROVINSI SULAWESI UTARA - Majampoh, Ester Lita Juniani; Saerang, David P. E.; Afandi, Dhullo (Universitas Sam Ratulangi, 2018)
Goods and services procurement by the government is an important activity in national development to increase public services and economic development. As a government institution, the General Election Committee must be able to account the goods and services procurement in the aspects of administration, technical, and finance. The research purpose is to analyze whether the goods and services procurement in the North Celebes Province General Election Committee is adequate or not. In this research are the explanation about local goods planning procedure and local goods procurement procedure in the North Celebes Province General Election Committee. The procedures are then analyzed by the internal control analysis from COSO and compliance analysis.Keywords : Planning, Procurement, sequacity.